IMPROVING THE INDONESIAN LANGUAGE SKILLS BY FOSTERING THE READING INTEREST OF 1ST GRADE STUDENTS - Sumiati Sumiati; Puji Astuti (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
Abstract Language skills are one of the keys to success in improving learning as a means to preparing oneself to enter the world of information. But in reality, there are obstacles that make language learning become less optimal at school. The lack of time to learn Indonesian at school makes students less able to understand the material presented by the teacher and the time used by the teacher to explain the material, so the students' learning activities become passive and not creative. With these conditions, it is expected that teachers will prepare more interesting teaching materials, which can stimulate student learning activities so the learning can be more fun. Indonesian Language learning is the learning that emphasizes language skills as a means to learn science. Reading is one form of obtaining scientific information, so it is necessary to deepen understanding of the language. Therefore, it is necessary to use the best possible learning time allocation to encourage students to understand a reading. However, students' low interest in reading makes it difficult to be implemented. This can be seen from the analysis results of their reading interest that only reached the average of 63.4%. After conducting the research in cycles I and II, there began to be a change in the increase of students' reading motivation, this was obtained from the reflection results every time the research was done which averaged by 81.4%, which indicates an increase of 18%.Keywords: Reading Interest; Indonesian Language Skills